Nanocellulose and Phycocyanin as Viable Additives for Electrospun Fibers: A Review of Functional Properties, Electrospinning Parameters, and Physicochemical Characterization - De Dios, Tabitha P. Vergel; Luares, Mia A.; Calibara, Myiesha Dane C.; Arboleda, Samuel Nelson G.; Estrellado, John Ray C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This literature review aims to highlight the developments and future directions in the use of nanocellulose and phycocyanin as electrospinning additives for biomedical applications, specifically in wound healing. Nanocellulose, a cellulose derivative known for its surface area, mechanical strength, and biocompatibility, is proposed as a sustainable alternative to enhancers of mechanical properties. Phycocyanin, a blue pigment from cyanobacteria, possesses anti-inflammatory, antioxidant, and antimicrobial properties, which may potentially enhance the performance of nanocellulose. The combination of the two components in electrospun fibers demonstrates significant promise for effective wound healing applications. However, progress is limited by the scarcity of experimental studies integrating both materials. One of the future directions of the study is improving the stability and shelf-life of phycocyanin within nanofibers, including approaches such as encapsulation and protective coatings. Scaling and manufacturing challenges, including high energy consumption and harsh chemical treatments in nanocellulose extraction, as well as the parameters of electrospinning, need to be addressed to enable mainstream commercialization. Further exploration of sustainable and purely physical extraction methods for nanocellulose is also critical for environmentally friendly alternatives to process scale-up and intensification.